-17-5n=8n-2(4+5n)

Simple and best practice solution for -17-5n=8n-2(4+5n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -17-5n=8n-2(4+5n) equation:


Simplifying
-17 + -5n = 8n + -2(4 + 5n)
-17 + -5n = 8n + (4 * -2 + 5n * -2)
-17 + -5n = 8n + (-8 + -10n)

Reorder the terms:
-17 + -5n = -8 + 8n + -10n

Combine like terms: 8n + -10n = -2n
-17 + -5n = -8 + -2n

Solving
-17 + -5n = -8 + -2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '2n' to each side of the equation.
-17 + -5n + 2n = -8 + -2n + 2n

Combine like terms: -5n + 2n = -3n
-17 + -3n = -8 + -2n + 2n

Combine like terms: -2n + 2n = 0
-17 + -3n = -8 + 0
-17 + -3n = -8

Add '17' to each side of the equation.
-17 + 17 + -3n = -8 + 17

Combine like terms: -17 + 17 = 0
0 + -3n = -8 + 17
-3n = -8 + 17

Combine like terms: -8 + 17 = 9
-3n = 9

Divide each side by '-3'.
n = -3

Simplifying
n = -3

See similar equations:

| 4(x+12)+5=9x-48 | | 12n+3=39 | | 2x^3+8=24 | | -2(x+4)=-3x+8 | | -31+18x-17X+9= | | 3(2r+5)-4(r-9)= | | -2(1+x)=7-5x | | b-4=-19 | | -7(-6b-5)=35-5b | | 6(2x-10)=0 | | 14+3d-7=12.10 | | -5(x+6)=5x-20 | | -(8+x)=-8+7x | | -18=18v | | 14x^2+10x-8=0 | | 2(t-4)-3(4t-5)=10-5(7t+3) | | 32+4m=-3(-5m-2)+2m | | -3(n-5)=15+4n | | 6x-2=3x-10 | | 4(1/4+x)=5 | | 7z-4=7z-z | | 6(1+7n)=40+8n | | 2x^2+9x=35 | | -4x^2(5x^2-21x-y)= | | 3(x-1)=-7(x-1) | | 1-5m=6(1-m) | | 7(3x+2)+22=36 | | -0.04x+1.32=1.08 | | 4(6x+5)=2+6x | | -3(4-y)=27 | | -1(3w-4)+12w=3w+4 | | 3m-5=5m+2 |

Equations solver categories